Problems of Eurocentric Views of History: An Examination of Certain Elementary Views about Colonialism in the Muslim World - Ahsan, Abdullah (ISTAC, 2013)
The 2011 Arab uprising have taken observers by surprise. Many expressed similar bewilderment over three decades ago when a revolutionary wave had shaken Iran. Why are the "pundits" of international politics so confused about the Muslim world? A student of history must ask why "experts" trained in social sciences and humanities have failed to envisage these events. In our opinion this has happened because of the Eurocentric view of history, particularly due to the misreading of the history of colonialism in the Muslim world. This paper examines the European historiography on the subject and explains the root cause problem. It concentrates on two issues: the question of economic exploitation and depence of the Muslim world on colonial powers and the question of Muslim commitment to identity and loyalty in the modern world. On the first question we would argue that Muslim world was made subservient to Europe by coercion and on the second, we wolud demonstrate that unlike Europe, Muslims never abandoned their ummah identity consciousness during and sfter their struggles for nationhood.